European Union and China´s competition for environmental leadership : Case study of the African region - Novosad, Matěj (2025)
In my thesis I examine the approaches and tools, which the European Union and the People´s Republic of China use to pursue environmental leadership in Kenya, and to what results. To answer my research questions, i conducted a qualitative content analysis of primary and secondary sources. The study shows that the EU Uses the attractiveness of the Single Market as an incentive, to achieve regulatory alignment. Producing tangible impacts on Kenya’s environmental institutions and policy frameworks. Whereas China by contrast, employs more of a development first approach centered around its BRI, achieving incredible results in infrastructural development, which generates rather mixed environmental outcomes